SELF-EFFICACY BASED SELF-CARE EDUCATION AND QUALITY OF LIFE AMONG WOMEN WITH EARLY MENOPAUSE: A QUASI-EXPERIMENTAL STUDY IN BOYOLALI REGENCY, CENTRAL JAVA, INDONESIA - Rahmawati, Ita; Dewi, Ratih Kumala; Dwihestie, Luluk Khusnul (IAKMI South Tangerang Branch, 2025)
Background: Early menopause significantly affects women’s hormonal balance, emotional stability, and social well-being, often leading to reduced quality of life. In Indonesia, awareness and support for women experiencing early menopause remain limited, highlighting the need for effective educational interventions. Objective: This study aimed to determine the effect of self-care education based on self-efficacy, empowerment, and their integration on the quality of life of women with Early menopause in Boyolali Regency, Central Java. Method: A quasi-experimental design was conducted involving 180 women aged 40–47 years who experienced Early menopause. Participants were divided into three groups: empowerment-based education, self-efficacy-based education, and integrated empowerment self-efficacy education. The intervention consisted of four 90-minute sessions over four weeks. Data were collected using the General Self-Efficacy Scale (GSES), Women Empowerment Scale (WES), and Menopause-Specific Quality of Life (MENQOL), and analyzed using Repeated Measures ANOVA with p < 0.05. Results: All groups showed significant improvement in quality-of-life scores after the intervention (p < 0.001), with no significant difference between groups (p > 0.05). Conclusion: Self-care education based on self-efficacy, empowerment, and their integration effectively improves quality of life among women with Early menopause and can serve as a practical community-based midwifery intervention.